Sarcocystis falcatula infection in ringneck parakeets (Psittacula krameri) in Minas Gerais, Brazil - Nascimento, Acácia Eduarda de Jesus; Silva, Nayara Toledo da; Carvalho, Tatyana Salarolli de; Bezerra, Gabriel Almeida de Oliveira; Souza, Lucas dos Reis; Oliveira, Ayisa Rodrigues de; Santos, Renato Lima (Brazilian Journal of Veterinary Pathology, 2024)
Sarcocystis falcatula is an Apicomplexa protozoan parasite recognized for its pathogenicity in birds. This microorganism has a complex life cycle involving definitive hosts, such as marsupials from the Didelphidae family, and intermediate hosts, which include a wide range of bird species. Three male ringnecks (Psittacula krameri) from a breeding facility with a history of sudden bird deaths were submitted for post-mortem examination. Gross findings included severe pulmonary congestion and edema, and diffusely congested livers. Histologically there was a severe and diffuse lymphohistiocytic interstitial pneumonia with moderate hyperemia and pulmonary edema. Numerous schizonts morphologically compatible with S. falcatula were observed in pulmonary endothelial cells, which were confirmed by immunohistochemistry. There was also moderate random multifocal lymphohistiocytic hepatitis, coalescing multifocal lymphohistiocytic and heterophilic myocarditis, mild coalescing multifocal lymphohistiocytic interstitial nephritis, and severe diffuse splenic congestion. These cases represent the first reported case of S. falcatula infection in ringnecks in Minas Gerais, highlighting the need for vigilance and control of Sarcocystis infections in captive bird populations.